Evaluating R&D networking to revitalize SMEs innovative performances: a management perspective - Basile, Alessandro (Business: Theory and Practice, 2012)
This research provides new evidence on the relationship concerning R&D networking decisions and firms’ competi-tiveness in a local SMEs entrepreneurial system. The role of R&D linkages on the firm’s productivity drivers and innovation processes is investigated and tested. Next, some empirical evidence, obtained by using detailed and specific survey-based data on 63 Italian SMEs, is presented. I find that R&D networking (R&D partnerships and agreements) has a moderate impact on the SMEs’ productivity and a strong impact on the innovation processes. Finally, in order to provide some practical implications based on this moderate finding, I present a R&D model to support the competitiveness of SMEs located in peripheral districts.